Youth in nation building: The way forward - Prasad, VRK (New Delhi D.P.S. Publishing House, 2022)
India's demographic advantage is going to last at least for another 25 to 30 years. The immense power and potential of the youth need to be harnessed by providing them with right knowledge and skills.
Keywords: Nation Building; Nation Development